DILEMATIKA ANTARA PERKAWINAN TUNGKU DENGAN ATURAN PERKAWINAN KATOLIK ROMA DI MANGGARAI - Adirusman Faran, Gabriel; Kebayantini, Ni Luh Nyoman; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
Topics that discussed in this thesis tells about the phenomenon of inbreeding marriage that happened to society of Nekang village, Manggarai, East Nusa Tenggara. Inbreeding marriages in the village community of Nekang is known as kawing tungku. Kawing tungku of Nekang village consists of three, that is tungku cu, tungku neteng nara, and tungku anak rona musi. As a majority of people who embrace Roman Catholicism, the kawing tungku of a Nekang village is strictly prohibited by the church. This rule is already contained in the canonical church. This phenomenon caused a dilemma for the people of Nekang village. Therefore, the Nekang villagers who married in a kawing tungku, the marriage could not be inaugurated by the church. Keyword: tungku, tungku cu, tungku neteng nara, tungku anak rona musi, kanonik